Secreted Dense Granule Adenine Nucleotides Promote Calcium Influx and the Maintenance of Elevated Cytosolic Calcium Levels in Stimulated Human Platelets - Lages, Bruce; Weiss, Harvey J. (Thrombosis and Haemostasis, 1999)
Evidence that secreted dense granule adenine nucleotides mediate part of the agonist-induced cytosolic calcium ([Ca2+]i) responses in human platelets was obtained from comparisons of fura-2-loaded platelets from normal subjects and from patients with a form of platelet storage pool deficiency (SPD) in which the secretory dense granules and their contents are virtually absent. SPD platelets had normal initial [Ca2+]i in creases induced by thrombin and the endoperoxide analog U46619, but a significantly enhanced decay of elevated [Ca2+]i levels following the initial increases. With thrombin, this enhanced [Ca2+]i decay was associated with decreased Ca2+ influx, as measured by Mn2+ quench of fura-2 fluorescence. Addition of micromolar concentrations of ADP, alone or together with ATP, after stimulation reversed the enhanced [Ca2+]I decay and increased Mn2+ quench in SPD platelets, but had no effect on these responses in normal platelets, while addition of 100-fold higher concentrations of ATP or apyrase before stimulation increased [Ca2+]I decay and decreased Mn2+ quench in normal platelets, but had little effect in SPD platelets. ATP and α,β-methylene ATP, a specific agonist for P2X1 receptors, at micromolar concentrations also increased Mn2+ quench, but to lesser extents than did ADP, in SPD platelets isolated and loaded with fura-2 in the presence of apyrase. Similar effects of ADP and excess ATP were seen in U46619-stimulated platelets, but decreased Ca2+ influx could not be measured directly in SPD platelets, presumably due to the very transient influx response seen with U46619. These results suggest that secreted dense granule ADP and ATP contribute to the maintenance of elevated [Ca2+]i levels, but not to the initial [Ca2+]i increases, in stimulated human platelets, most likely via a nucleotide-specific component of Ca2+ influx which may be mediated by interactions with both P2X1 and P2Y1 purinoceptors.